Thalamocortical circuits and functional architecture - Kremkow, Jens (Annu Rev Vis Sci, 2018)
The thalamocortical pathway is the main route of communication between the eye and the cerebral cortex. During embryonic development, thalamocortical afferents travel to cortical layer 4 and are sorted by receptive field position, eye of origin and contrast polarity (preference for light or dark stimuli). In primates and carnivores, this sorting involves a large number of afferents most of which sample a limited region of the binocular field. Devoting abundant thalamocortical resources to process a limited visual field has a clear advantage: it allows sampling a large number of stimulus combinations at each spatial location. Moreover, the sampling efficiency can be further enhanced by organizing the afferents in a cortical grid for eye input and contrast polarity. We argue that thalamocortical interactions within this eye/polarity grid can be used to represent multiple stimulus combinations found in nature and build an accurate cortical map for multi-dimensional stimulus space.